Strategi Pengembangan Usaha Mikro Kecil Menengah (UMKM) V-Fie Bakery dengan Pendekatan Business Model Canvas (BMC) - Livia Anggraeni; Putri Alifia; Deasy Rizky; Retno Indriartiningtias (Metris: Jurnal Sains dan Teknologi, 2025)
UMKM V-Fie Bakery is a manufacturing business focused on producing cakes and bread. This study aims to develop the business and map the business model of V-Fie Bakery using the Business Model Canvas (BMC) approach. The research was conducted using a descriptive qualitative method through interviews with the business owner as the primary data source. UMKM V-Fie Bakery was selected because it faces various challenges in business management, making it important to analyze its business model comprehensively. The identification results show several issues across the nine BMC elements, including dependence on a single main supplier and limited partnerships (key partners), suboptimal digital promotion (key activities), limited production capacity and employee skills (key resources), product value that is not yet aligned with its price (value propositions), the absence of a customer loyalty system (customer relationship), a narrow market segment (customer segments), distribution channels that do not yet include delivery services (channels), relatively high operational costs (cost structure), and revenue streams that are not yet diversified (revenue streams). Through development analysis, improvements were proposed for all elements, including expanding partnerships with schools, offices, and delivery service providers; enhancing promotional activities and employee training; adding additional skills as key resources; providing bundling packages and seasonal promotions; implementing a membership card; expanding customer segments to include children; adding delivery order services; and diversifying income through hampers and snack box packages. Based on the overall results, UMKM V-Fie Bakery demonstrates strong growth potential if the recommended development strategies for each BMC element are implemented consistently.